2014
DOI: 10.33225/pec/14.59.07
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Social Aspects of Teacher Burnout in Georgia

Abstract: The study aimed to identify personal and social factors having impact on teacher burnout in Georgia. The survey was conducted on 373 Georgian school teachers. Teacher burnout phenomena was studied in connection with psychological factor such as locus of control and social factors - school climate dimensions: Principals' attitude to teachers, teachers' attitude to colleagues and to students. Qualitative and quantitative methods were used for the research. The highest teacher burnout was identified on Emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Second, it was found that the problem of teacher burnout has a negative correlation with the school climate and school culture, and that the problem of teacher burnout has a negative impact on the school climate and school culture [22,[37][38][39]. School climate is the personality of a school organization that has a different feeling or uniqueness for each school [40] and means the norms and expectations shared by school members [41].…”
Section: Teacher Burnout Problem Class School Climate and School Culturementioning
confidence: 99%
“…Second, it was found that the problem of teacher burnout has a negative correlation with the school climate and school culture, and that the problem of teacher burnout has a negative impact on the school climate and school culture [22,[37][38][39]. School climate is the personality of a school organization that has a different feeling or uniqueness for each school [40] and means the norms and expectations shared by school members [41].…”
Section: Teacher Burnout Problem Class School Climate and School Culturementioning
confidence: 99%